2015
DOI: 10.1061/(asce)me.1943-5479.0000357
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Stable Strategy for Postdisaster Insurance: Game Theory Approach

Abstract: Natural disasters leave the impacted regions with financial burdens both on the individual and governmental levels. Thus, the goal of the associated stakeholders is to maximize the host communities' welfare through minimizing their post-disaster financial burdens. Accordingly, this paper attempts to find a post-disaster insurance plans equilibrium so as to mitigate the financial impacts associated with the natural disasters. Utilizing an evolutionary game theory approach, the equilibrium is investigated betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 27 publications
(19 reference statements)
0
29
0
Order By: Relevance
“…Post-disaster insurance policies also affect the recovery processes (Eid et al 2015;Olshansky et al 2006), and have been reported as a key factor in the success of redevelopment projects because it provides adequate financial means for recovery (NDRF 2011;Olshansky et al 2006). To this extent, to optimize the various disaster recovery strategies, one should understand and account for the complex interactions among the different multisector stakeholders (Eid and El-adaway 2016a).…”
Section: Sustainable Disaster Recovery and Social Vulnerabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Post-disaster insurance policies also affect the recovery processes (Eid et al 2015;Olshansky et al 2006), and have been reported as a key factor in the success of redevelopment projects because it provides adequate financial means for recovery (NDRF 2011;Olshansky et al 2006). To this extent, to optimize the various disaster recovery strategies, one should understand and account for the complex interactions among the different multisector stakeholders (Eid and El-adaway 2016a).…”
Section: Sustainable Disaster Recovery and Social Vulnerabilitymentioning
confidence: 99%
“…Disasters are defined as "nonroutine events in societies : : : that involve conjunctions of historical conditions and social definitions of physical harm and social disruption" (Picou et al 2004). Disaster events have led to billions of dollars in infrastructure losses because of their increasing rates and magnitudes in the last decade (Eid et al 2015;Economics of Climate Adaptation Working Group 2009). Recent examples in the United States include: (1) Hurricane Andrew in 1992 ($20.9 billion); (2) the Northridge earthquake in 1994 ($15.9 billion); (3) the four Hurricanes Charlie, Ivan, Frances, and Jeanne in 2004 (total of $21.9 billion); (4) Hurricane Katrina in 2005 ($125 billion); (5) Hurricane Rita in 2005 ($10 billion); (6) Hurricane Wilma, also in 2005, ($16.8 billion); (7) Hurricane Ike in 2008 ($19.3 billion); and (8) Hurricane Sandy in 2012 ($68 billion) (Eid et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is understood that the insurers follow a risk assessment in their objective functions. Nevertheless, following Eid et al (2015), an evolutionary game theory approach can be utilized to determine a stable postdisaster insurance profile between residents and insures that would increase both their utility functions…”
Section: State Disaster Recovery Coordinatormentioning
confidence: 99%
“…At the initial step, the residents were uniformly distributed among the three insurance companies along with the no insurance option. Through the utilization of MPS as a social learning technique, as previously discussed, and following the game theory proposed by Eid et al (2015), the residents changed their choices to attain the highest possible objective function through mimicking the fittest set of residents among them.…”
Section: Residents' Choices Of Different Insurance Companiesmentioning
confidence: 99%
“…Naderpajouh et al (2014) used it in risk management between developer and opposition in infrastructure developments. Also, game theory has been used in the payment problems (Wu et al 2011), renewal of construction objects (Antuchevičiene et al 2006), cooperation during project delivery (He et al 2016), and post-disaster management (Eid et al 2015). Even some researchers have used game theory in studying the delayed projects (Castro et al2007;Estévez-Fernández 2012).…”
Section: Dispute Resolution Methodsmentioning
confidence: 99%